Pre-germination treatments on kidneywood (Eysenhardtia polystachya) seeds - Angélica Lorenzo-Barrera, Norma (2023)
Kidneywood (E. polystachya) is a medicinal plant used for urinary and digestive system infections and inflammations in humans and animals. In addition, kidneywood is used as fodder and its wood is employed in rural housing construction. Populations of this plant have been reduced by the extraction that occurs in its natural habitat; in addition, the germination of its seeds is slow. To improve its germination, this research aimed to evaluate the effect of pre-germination treatments on seed germination and seedling growth of E. polystachya. Seven pre-germination treatments and a control were evaluated in a completely randomized experimental design with four replicates per treatment and 25 seeds per replicate. The results indicated that all treatments applied to the seeds produced higher germination percentages (100 to 182%) and greater seedling growth (14,6 to 59,8% more in height) than the control, with the exception of soaking in water. The pretreatment that generated the best response was the application of AG3 at 600 ppm for 30 min, with 96% germination, 19,4 cm height, 3,9 mm stem diameter, 20 cm root length, 21 leaves per plant and 375 mg dry matter per seedling. Mechanical scarification generated 86% germination, 16,1 cm height, 2,9 mm stem diameter, 18 cm long roots, 12,5 leaves, and 354 mg dry matter, added to which it initiated emergence in less time (3,7 d), also making it a good and less costly option.